The relationship between working in the “gig” economy and perceived subjective well-being in Western Balkan countries - Vučeković, Miloš; Avlijaš, Goran; Marković, Mirjana Radović; Radulović, Dejan; Dragojević, Arsen; Marković, Dušan (Frontiers in Psychology, 2023)
The combination of accelerated digitalization and the recent COVID-19 crisis has increased the number of remote workers worldwide to unimaginable proportions. Among the large number of remote workers that execute their projects from home, there is a significant number of permanently self-employed remote workers, usually referred to as freelancers. Despite the importance of this kind of business activity for modern project management society, perceived drivers of freelancing are still unknown. The goal of this paper was to shed some light on the general subjective well-being of freelancing activity and investigate differences concerning gender, age, and education. The study was performed in late 2020 and included 471 freelancers from Serbia, Bosnia and Herzegovina, Macedonia, and Montenegro that participated in an online questionnaire evaluating their subjective well-being while participating in the “gig” economy. Factor analysis was used as a primary statistical method and two major groups were identified: (1) Impact of working from home on a freelancer’s personal life and health and (2) Fulfillment of expectations in the economic and professional sense. Gender was found not to be significant for overall work satisfaction. However, older freelancers proved to be more satisfied with the fulfillment of economic and professional expectations, which correlate with years of professional experience. Another conclusion is that more educated freelancers are generally less satisfied with both groups of drivers - fulfillment of personal life and professional expectations. Understanding how the combination of occupations, technological infrastructure, and demographic characteristics in the region has affected the well-being of freelancers may help policymakers and organization owners, as well as future entrepreneurs, better prepare for this model of work in the future. It also increases the possibility of exploring individual dimensions of wellbeing useful for targeting interventions at the level of each country separately. In line with this, the present study contributes to the existing body of knowledge and the impact of hybrid models of work on the subjective well-being of workers in the “gig” economy.